Cleaning the Ganga: rethinking irrigation is key - Shah, Tushaar; Rajan, Abhishek (2019)
Prioritising aviral dhara (uninterrupted flow) over nirmal dhara (unpolluted flow) can deliver quick outcomes in the Namami Gange Programme. Treating human, municipal and industrial waste released into the Ganga is a long-term project requiring vast resources and political energy, besides behavioural change on a mass scale. But, Ganga’s dry season flows can be quickly improved by basin-scale conjunctive management of the surface water and groundwater. Irrigation in the Ganga basin today depends on tubewells far more than canals. A multipronged protocol is outlined to manage the old canal network and new hydropower storages in order to maximise irrigation benefits and improve dry season river flows.